PIEZO ion channel is required for root mechanotransduction in Arabidopsis thaliana - Mousavi, Seyed A. R. (Proc Natl Acad Sci U S A, 2021)
Plant roots adapt to the mechanical constraints of the soil to grow and absorb water and nutrients. As in animal species, mechanosensitive ion channels in plants are proposed to transduce external mechanical forces into biological signals. However, the identity of these plant root ion channels remains unknown. Here, we show that Arabidopsis thaliana PIEZO1 (PZO1) has preserved the function of its animal relatives and acts as an ion channel. We present evidence that plant PIEZO1 is expressed in the columella and lateral root cap cells of the root tip, which are known to experience robust mechanical strain during root growth. Deleting PZO1 from the whole plant significantly reduced the ability of its roots to penetrate denser barriers compared to wild-type plants. pzo1 mutant root tips exhibited diminished calcium transients in response to mechanical stimulation, supporting a role of PZO1 in root mechanotransduction. Finally, a chimeric PZO1 channel that includes the C-terminal half of PZO1 containing the putative pore region was functional and mechanosensitive when expressed in naive mammalian cells. Collectively, our data suggest that Arabidopsis PIEZO1 plays an important role in root mechanotransduction and establish PIEZOs as physiologically relevant mechanosensitive ion channels across animal and plant kingdoms.